Peningkatan Kepuasan Kerja Aparatur Sipil Negara (ASN) bagian Prasarana dan Penyuluhan Pertanian berbasis Budaya Organisasi dan Gaya Kepemimpinan Transformasional pada Intansi XYZ - Indra Anggara; Aam Rachmat Mulyana (Journal of Management and Bussines (JOMB), 2024)
This research aims to understand the relationship between organizational culture and transformational leadership style on job satisfaction of State Civil Service (ASN) employees in the agricultural infrastructure and extension section at XYZ agency. The research method used is quantitative with a sampling technique using the entire population as a sample. Data was collected through questionnaires and interviews, then analyzed using descriptive and associative techniques as well as multiple regression analysis using the SPSS version 25 program. The research results showed that partially, organizational culture and transformational leadership style had an influence on employee job satisfaction. Simultaneously, these two variables also influence the job satisfaction of employees in the agricultural infrastructure and extension department at XYZ agency. The conclusion is that the importance of good organizational culture and transformational leadership style in increasing ASN job satisfaction, especially in the agricultural infrastructure and extension environment. Keywords: State Civil Servants (ASN), Organizational Culture, Transformational Leadership Style, Job Satisfaction